Kontrol PID Untuk Keseimbangan Bola Ping-Pong Dengan Sensor Ultrasonik Dan Motor Servo Berbasis Labview - Ivan Candra Utama (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2016)
Abstract - The balancing ball system is a system where there is a ball that can move freely on a rod and the position of the ball move can be adjusted automatically according to the desired set point. The balancing ball system is a very important system in studying the control system. This is because the balancing ball system is an unstable system where the output of the system (ball position) always increases indefinitely for each input (rod angle) with a fixed value. Therefore, ball balancing systems require complex control theories. To be able to stabilize the balancing ball system, a controller is needed. In order to get the best controller, tuning the Integral Derifative (PID) controller parameter is done. In this tuning we can know the value of proportional gain (Kp), integral time (Ti) and derivative time (Td). The PID controller will give action to the balancing ball control based on the error obtained, the distance between the ultrasonic sensor and the desired ball is called the set point. LabVIEW software is used as a monitor, servo motor speed control. Keyword : Labview, Balance Ball, Arduino, Motor Servo, Ultrasonic Sensor